Seismic Evidence of Magmatic Rifting in the Offshore Taupo Volcanic Zone, New Zealand. Issue 22 (27th November 2019) - Gase, Andrew C.; Van Avendonk, Harm J. A.; Bangs, Nathan L.; Luckie, Thomas W.; Barker, Daniel H. N.; Henrys, Stuart A.; Bassett, Dan; Okaya, David A.; Jacobs, Katrina M.; Kodaira, Shuichi; Fujie, Gou; Arnulf, Adrien F.; et al.
Abstract: Relationships between extensional tectonics and magmatism are ubiquitous in continental rifts and oceanic spreading centers. Yet few studies document interactions between extensional faults and mantle melts in volcanic arcs. We constrain the crustal structure of the extensional offshore Taupo Volcanic Zone (TVZ) from a marine multichannel and wide‐angle seismic experiment. The TVZ crust thins from >26 km to ∼18–19 km across ∼50 km in the Bay of Plenty. Elevated P wave velocities in the lower crust indicate mafic additions. Magmatic sills between 4‐ and 15‐km depth lie beneath listric normal faults in a ∼40‐km‐wide active rift zone. P wave velocities in the middle and upper crust along the arc front are ∼0.3–0.5 km/s slower than in the adjacent crust, indicating a possible thermal anomaly imparted by heat from magmatic intrusions. We propose that rifting in the offshore TVZ is partially compensated by intrusions and assisted by thermal weakening of the lithosphere. Plain Language Summary: The offshore Taupo Volcanic Zone is a rifting volcanic arc located in the North Island of New Zealand. We use seismic waves from man‐made sources to map seismic wave speeds and image fault and magma‐related structures beneath the offshore Taupo Volcanic Zone. We find that rifting has stretched the crust from >26 km to ∼18–19 km. Fast seismic wave speeds in the lower crust suggest that magma has partially filled some of the stretched crust to reduce the amount of thinning. Using seismic reflections, we find that the zone with the largest faults coincides with an area of intruded magma located between 4‐ and 15‐km depth. We propose that a feedback relationship influences the locations of faults and magma. Extension helps magma to rise from deep in the Earth. In response, the intruded magma heats and weakens the rigid outer layer of the earth to assist more rifting. The hazard potential of the fault and magma systems in this region is not fully known, motivating the need for further investigations to map and monitor magma bodies and faults in the offshore Taupo Volcanic Zone. Key Points: Magmatic intrusions and thermal weakening may facilitate rifting in the offshore Taupo Volcanic Zone Bay of Plenty crust rifted from >26 km to ∼18–19 km across a 50‐km‐wide zone; magmatic additions compensate ∼20–30% of crustal extension Listric faulting overlies an ∼40‐km‐wide zone of sill complexes and heterogeneous P wave velocities in the upper and middle crust